Dampak Pandemi Covid-19 Terhadap Pengalaman Soundscape Di Taman Dewi Sartika Bandung - Aldo Golfana Topan Rachardjo; Roni Sugiarto (Universitas Sebelas Maret Surakarta, 2022)
This research aims to explore the extent to which the Covid-19 pandemic with all kinds of restrictions that occur affects the soundscape experience, and explores the extent to which an audial study was created at Taman Dewi Sartika Bandung as a thematic city park in the center of Bandung City. This is deemed necessary so that practical and theoretical contributions are not only limited to visual goals but also give meaning to audial experience. The soundscape approach has not been widely applied in the architectural design process, especially in urban parks in the city center in Indonesia, particurarly in Bandung. This research was conducted by using observations at Dewi Sartika Park, and used a qualitative and quantitative approach, accompanied by an exploratory literature review on soundscapes, city parks as part of public space, and human perception. Through this research, it was found that the presence of the COVID-19 pandemic has changed the soundscape experience and shifted the existence of the park from being very cultural, namely domination in aspects of activity and place, to being very natural which is